(untitled) (Journal of Asian Development Studies, 2025)
Due to increased technological advances in the area, retailers are experiencing complexities in their supply chain and searching for ways to improve it and bring down operations costs. AI is receiving tremendous attention in the modern world as a cutting-edge technology that can replace manual efforts, machine learning and predictive analytics for supply chain efficiency. This paper shows how AI can be applied in e-commerce logistics regarding demand forecasting, warehouse automation, route optimization, and detection. A cross-sectional questionnaire was used with responses from 300 professionals in the supply chain field, procuring a richness of quantitative data regarding the advantages and disadvantages of incorporating AI within supply chains. Based on the study, automation increases efficiency, especially in the warehouse, by 85% and in the route estimation by 82%. AI also saves substantial costs within areas such as inventory and transportation, which can have cost cuts of around 30 to 40 per cent. Nevertheless, challenges, which include high implementation costs, shortage of skilled talent, data privacy and protection issues, reduce the uptake of Artificial Intelligence. Nonetheless, further investments in real-time AI analytics, autonomous logistics, and AI-supported sustainability projects open up the possibility of the continuing integration of AI into supply chain management. In addition to analyzing the current state of AI development in e-commerce logistics, this research offers recommendations to companies interested in implementing AI-based solutions to enhance supply chain management.